2016
DOI: 10.2215/cjn.02190216
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Dialysis Vascular Access: What Is the Optimal Vascular Access Type and Timing of Access Creation in CKD and Dialysis Patients?

Abstract: Optimal vascular access planning begins when the patient is in the predialysis stages of CKD. The choice of optimal vascular access for an individual patient and determining timing of access creation are dependent on a multitude of factors that can vary widely with each patient, including demographics, comorbidities, anatomy, and personal preferences. It is important to consider every patient's ESRD life plan (hence, their overall dialysis access life plan for every vascular access creation or placement). Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 78 publications
1
93
0
3
Order By: Relevance
“…La elección del acceso vascular óptimo para un paciente individual y el tiempo de creación dependen de factores que varían ampliamente con cada paciente, como datos demográficos, comorbilidades, anatomía y preferencias personales. 13 Los datos publicados recientemente del estudio Dialy Outcomes and Practice Patterns (DOPPS 5) mostraron un alto porcentaje de CVC y un bajo porcentaje de uso de FAV (67% y 28%, respectivamente) en pacientes con accesos vasculares de hemodiálisis en EEUU. El estudio IDEAL hace referencia que con una filtración glomerular entre 10-15 ml/min/1,73 m2 con pacientes adecuados casi siempre hay tiempo para la creación de una FAV.…”
Section: Inicio De Diálisis Con O Sin Una Favunclassified
“…La elección del acceso vascular óptimo para un paciente individual y el tiempo de creación dependen de factores que varían ampliamente con cada paciente, como datos demográficos, comorbilidades, anatomía y preferencias personales. 13 Los datos publicados recientemente del estudio Dialy Outcomes and Practice Patterns (DOPPS 5) mostraron un alto porcentaje de CVC y un bajo porcentaje de uso de FAV (67% y 28%, respectivamente) en pacientes con accesos vasculares de hemodiálisis en EEUU. El estudio IDEAL hace referencia que con una filtración glomerular entre 10-15 ml/min/1,73 m2 con pacientes adecuados casi siempre hay tiempo para la creación de una FAV.…”
Section: Inicio De Diálisis Con O Sin Una Favunclassified
“…This workshop included nephrologists, surgeons, radiologists, basic scientists, and industry representatives with a common interest in vascular access research. This Moving Points series features three reviews related to topics presented at this workshop (3)(4)(5).…”
mentioning
confidence: 99%
“…In a systematic review of 168 contemporary randomised trials in HD, function was the most frequently reported vascular access outcome (81% of trials) followed by infection (38%), yet function was the most heterogeneous outcome and measured in nearly 500 different ways 178 For example, monitoring the rate of vascular access interventions needed to maintain its use for HD as a measure of function rather than targeting a percentage of AVF and CVC use may be recommended. This is a more patient-centred goal of finding the optimal vascular access requiring the least number of procedures to provide adequate dialysis 238,239 . Incentivising a reduction in interventions is anticipated to reduce healthcare costs and hospitalisations while simultaneously reducing the burden of invasive, often painful and anxiety-provoking procedures that are disruptive to the patients' lives 8,181 .…”
Section: Discussionmentioning
confidence: 99%
“…The former entails a more individualised vascular access selection (i.e. "the right access for the right patient at the right time for the right purpose" 239,258 ) taking into consideration the patient's preference and outcome priorities and making use of refined prediction tools to better inform the optimal access choice 259 . The latter requires further research and optimisation of integrated care delivery, education, training, surgical-and cannulation skills, and surveillance combined with targeted therapies and would be best evaluated with innovative adaptive trial designs (e.g.…”
Section: Exploration Of Mechanistic Pathways Of Avf Failurementioning
confidence: 99%
See 1 more Smart Citation